Entrepreneurial management and employee-driven innovative work practices - Hytti U; Aaltonen S (My University, 2022)
Entrepreneurial managementand employee-driven innovative work practices
Abstract presented at the track: Leadership and Innovation
Research problem: Innovation is a key for growth and competitiveness in small firms (Calantone et al. 2002, Freel & Robson 2004, Wolff & Pett 2006). Innovation has been extensively studied in the small firm context but mainly as an attribute of the organization or through the abilities the entrepreneur/entrepreneurial team. Currently, innovation studies focus on the role of employees in generating and contributing to the innovations. There seems to be a gap in the literature addressing employees’ innovative work practices in the small firm context. Based on previous literature it is possible to assume two divergent realities in small, entrepreneur-led family businesses. On one hand these flat and informal organisations may leave a lot of room for employee initiative and activity. On the other hand, the strong entrepreneurial leadership may crowd out employee activity. In this study we will investigate the continuities and disruptions between entrepreneurial leadership and employee-driven innovative work practices in small family businesses.
Theory: The study relies on the concept of ‘practice’ in business research (e.g. Whittington 2006; Eriksson et al. 2008a; 2008b; Laine 2009, Laine and Vaara 2010). A key argument in this debate is that ‘what practitioners do in practice’ cannot be understood with the main stream management and organization theories, which do not acknowledge practitioners as experts of their own work (Salaman and Storey 2002), nor pay attention to organizational work as ‘practice’ (Dougherty 2006).
Methodology: The study is carried out as a case study in two innovative small family businesses in the Turku region. The first case is a food production company that is managed by the owner-manager. The second case is from a manufacturer of medical devices managed by a hired CEO. In this study we understand entrepreneurship leadership and employee work as practices. The research materials include interviews and observation materials in the two organisations. In the analysis our focus is on the practices and the kind of realities they produce.
Results: Based on the preliminary findings it seems that the strong entrepreneurial leadership practice may not leave much room for employee activity. The owner-manager’s daily visits to the operations and close attention to every detail do not leave much room for or do not invite employee initiative. In the other company that has recently hired the first external CEO much focus has been placed on giving additional responsibility and delegating tasks to employees. As a downside the decision-making has become slower.
Conclusions: This paper contributes to generating new knowledge and understanding of the continuities and disruptions between two spheres: strong entrepreneurial leadership practice and employee-driven innovative work practices. While in previous literature both are presented as important elements in innovation, it is less clear how and under which conditions they can co-exist.
RENT XXVII conference ‘Research in Entrepreneurship and Small Business: Entrepreneurship, Institutions and Competitiveness’, Vilnius 20-22 November 2013